Wall a Platform for Forming Dialogue in the City, How is the Wall Effective in Democratizing the City Space? - Mohammad Reza Sartipi Isfahani (منظر, 2023)
One of the (apparently) most well-known elements of architecture and urban planning is the wall, and much has been written about its features and characteristics. A physical-functional element that also has meanings and myths in its core, and in this respect, it can be seen from the examples of landscape; considered as an objective-mental phenomenon. The wall, especially in the architecture of Iranian buildings and gardens, is an integral part of the concept of these spaces and perhaps it is very difficult to imagine an Iranian garden or house without a wall. Adjusting the air and creating a microclimate, protection against adverse and harsh weather outside, wild animals and thieves, sacred protection against the entry of the devil, and other important features are the characteristics of this fundamental element of Iranian architecture. Sometimes these walls are made as clay for village garden alleys, and sometimes they form the high and stable walls of the Karimkhani Citadel, sometimes it is a simple wall without decoration, and sometimes it is decorated with all kinds of flower arrangements, brickwork, tiling, and other Iranian decorative arts (although In general, the wall in Iranian culture is simple and unpretentious, and if there is a decoration, it is mostly for the entry of the complex or building), sometimes they are rigid and impenetrable, and sometimes they expose the transparent with the function of Safavid-era Tajir gardens walls to the visitors. One of these characteristics, which is perhaps less discussed, is the potential of expressing the views of citizens. The wall is a “popular media” with a large audience on the scale of a city’s landscape, which is usually not paid attention to, or they express a specific point of view in society in a structured and structured way, and in this sense, they violate freedom of expression. Now the question that arises is why the wall in most cases (except for special times such as street protests), works incompletely if it can help the society in the direction of becoming more democratic.